PENGARUH VARIASI PENAMBAHAN KADAR AIR DENGAN BAHAN PENGIKAT BENTONIT TERHADAP KARAKTERISTIK PASIR CETAK DAN CACAT POROSITAS HASIL PENGECORAN LOGAM PADUAN Al-Si - Fajar Rizki Saputra; Budi Harjanto; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
The purposes of this research was to learns (1) the effect of adding moisture content to the permeability of sand casting; (2) the effect of adding moisture content to the compressive strength of sand casting; and (3) the effect of adding moisture content to porosity defects in casting results. This research is conducted at Manufacturing Polytechnic, Ceper, Klaten. The method that used is pre-experimental design with design one-shot case study. The independent variable in this research are variations of moisture content of 4%, 6%, and 8%, with the dependent variable are permeability and compressive strength of sand casting, and porosity defect of Al-Si alloy cast. The permeability test by using permeability meter, compressive strength test by using universal strength machine¸ and porosity defect test of cast result on qualitative with visual observation and quantitative with calculation of porosity percentage.  The results of  the adding of moisture content  of 4%, 6%, and 8% in the sand casting showed that: (1) The higher the addition of water measure on sand casting decrease the permeability value. The highest permeability value in the addition of 4% water measure is 103.67 cm3/min, while the lowest in the addition of 8% water measure is 83.00 cm3/min; (2) The higher water content in the printed sand further decreases the value of its compressive strength. The lowest compressive strength value occurred at 8% water measure increase of 39.00 KN/m2, while the highest value of compressive strength was obtained at 4% water measure addition 47.56 KN/m2; (3) The higher water measure of sand casting will result in a higher percentage of porosity defects on the casting results. The lowest percentage of porosity defect was obtained by adding 4% water measure is 1.56% from total volume, while the highest was 8% water measure is 3.06% from total volume.